2004
DOI: 10.1021/jp036658r
|View full text |Cite
|
Sign up to set email alerts
|

Raman Investigation of the N2−O2 Binary System as a Function of Pressure and Temperature

Abstract: We produced mixtures of N2-O2 with different concentrations and performed low-temperature Raman studies at ambient and high pressures. From spectra in vibron and phonon regions, we determined band frequency, bandwidth, and band intensity as a function of temperature, pressure, and concentration. We determined the vibron Raman cross-sections and deduced the true concentrations of mixtures from vibron Raman band intensities. These concentrations were different from those determined from partial gas pressure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In Raman studies the real concentration is easily found from relative intensities in Raman spectra and known Raman cross sections for vibrations (see Fig. 2 in [8]). In FTIR studies about N 2 -O 2 mixtures [9], which are IR inactive, we determined the actual concentration by means of chromatography and mass-spectrometry; after measurements the sample was evaporated into a test volume and was then analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…In Raman studies the real concentration is easily found from relative intensities in Raman spectra and known Raman cross sections for vibrations (see Fig. 2 in [8]). In FTIR studies about N 2 -O 2 mixtures [9], which are IR inactive, we determined the actual concentration by means of chromatography and mass-spectrometry; after measurements the sample was evaporated into a test volume and was then analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid partial demixing in the gas-liquid region (see Fig. 2 [1]) and via contact between vapors over the sample and the gas mixing system we followed here another strategy. The cell temperature was set at T = 11 K, and the cell was filled with the immediately freezing gaseous mixture (couple of seconds), so that there was no chance for a concentration change.…”
Section: Methodsmentioning
confidence: 99%
“…Mixtures of these components were much less studied on the contrary, because of several reasons: due to the complexity in results after pure systems, due to missing theoretical modeling, due to problems in producing samples with sufficiently good crystal quality. In a recent paper [1] we could prove that discrepancies in published phase diagrams T-x% of N 2 -O 2 [2,3] are most likely due to thermodynamic instable samples. The general aim of this paper [1] was to deduce from fingerprints in vibron and phonon spectra lines of phase transitions, to prove reproducibility and reliability of our statements by cooling/heating cycles, to determine quantitatively from relative Raman vibron band intensities the solubility of N 2 in O 2 or vice versa.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations